QUALITATIVE DETECTION OF LEAD IN FORTIFIED WATER SAMPLE BYAPAPERCHROMATOGRAPHIC ENZYME INHIBITION TECHNIQUE - KUMAR, N.V. NANDA; G. SEETHAMMA (The Bioscan, 2007)
Chick heads thrown out as biowaste were employed as a enzyme source for the detection of lead compounds by an enzyme inhibition technique on paper chromatograms. The lead compounds (lead nitrate and lead acetate) appeared as white spots on a pink back ground due to the inhibition of chick brain succinate dehydrogenase employing a chromogenic reagent mixture containing sodium succinate substrate, (2-(4-Iodophenyl)-3-( 4-nitrophenyl)-5 phenyl tetrazolium chloride and N-methyl phenazonium metho sulphate. The minimum detectable amounts were about 5 µg of lead nitrate and 5 µg of lead acetate. Many other animal succinate dehydrogenases also gave inhibition spot under the same conditions on chromatograthic paper but they were less sensitive than chick brain succinate dehydrogenase. Water sample was fortified with lead nitrate and lead acetate and were detected by enzyme inhibition technique.